Some Old Movies Become Classics – A Case Study Determining the Scientific Value of ROV Inspection Footage on a Platform on Australia’s North West Shelf - Thomson, Paul G.; Fowler, Ashley M.; Davis, Andrew R.; Pattiaratchi, Charitha B.; Booth, David J. (Frontiers in Marine Science, 2018)
The global oil and gas industry holds a vast archive of Remotely Operated Vehicle (ROV) inspection footage potentially containing useful long-term data on marine biological communities. With the upcoming era of decommissioning of oil and gas structures, it is timely to assess the usefulness of this footage for researching these communities. We used ROV inspection footage to characterise the sessile invertebrates and fishes associated with the Goodwyn Alpha Production Platform (GWA) on the North West Shelf of Australia between depths of 10 and 125 m during 2006 and 2008. Depth was a major driver of invertebrate assemblages, most likely due to specific requirements such as light, and differences between years were most likely from the physical detachment of species by cyclones and internal waves. Phototrophic species were mostly limited to the upper 50 m of the platform, including the hard coral Pocillopora sp. and the soft corals Nephthea sp. and Scleronephthya sp. In contrast, heterotrophic species including sponges, anemones, bryozoans, hydroids, bivalves such as Lopha folium. and the hard coral Tubastrea spp., were distributed across all depths. We observed 1791 fish from at least 10 families and 19 species, including commercial species such as crimson seaperch (Lutjanus erythropterus), red emperor (L. sebae), saddle-tailed seaperch (L. malabaricus), mangrove jack (L. erythropterus) and trevally (Caranx spp.). Fish density increased significantly with depth during 2008, from a mean of 23 fish/50 m2 between 10 – 25 m to 3373 fish/50 m2 at 125 m, where small unidentified baitfish were abundant. The highest densities of commercial species occurred between 25 – 75 m depth, suggesting that mid-depth platform sections had high habitat value, a consideration when selecting decommissioning options. The greatest difficulties using the video were the poor lighting and resolution that inhibited our ability to identify sessile species with high taxonomic precision. However, the footage was useful for evaluating high-level biodiversity of the platform, understanding how fish and invertebrate communities changed with depth and comprehending the dynamic nature of the invertebrate community over time. Understanding the habitat value of structures will be necessary for making environmentally-sound decommissioning decisions in the future.